2014
DOI: 10.1002/chem.201403302
|View full text |Cite
|
Sign up to set email alerts
|

Domino‐Hydroformylation/Aldol Condensation Catalysis: Highly Selective Synthesis of α,β‐Unsaturated Aldehydes from Olefins

Abstract: A general and highly chemo-, regio-, and stereoselective synthesis of α,β-unsaturated aldehydes by a domino hydroformylation/aldol condensation reaction has been developed. A variety of olefins and aromatic aldehydes were efficiently converted into various substituted α,β-unsaturated aldehydes in good to excellent yields in the presence of a rhodium phosphine/acid-base catalyst system. In view of the easy availability of the substrates, the high atom-efficiency, the excellent selectivity, and the mild conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 90 publications
0
8
0
Order By: Relevance
“…Therefore, the combination of transition metal‐catalysed hydroformylation with further reactions is still a field of high interest in chemistry as seen in reports that have been recently published 3. The specific combination of hydroformylation with organocatalytic reactions is displayed only in few examples4 with a main focus on tandem hydroformylation/aldol reaction4ad.…”
Section: Development Of the Tandem Hydroformylation/acyloin Reaction mentioning
confidence: 99%
“…Therefore, the combination of transition metal‐catalysed hydroformylation with further reactions is still a field of high interest in chemistry as seen in reports that have been recently published 3. The specific combination of hydroformylation with organocatalytic reactions is displayed only in few examples4 with a main focus on tandem hydroformylation/aldol reaction4ad.…”
Section: Development Of the Tandem Hydroformylation/acyloin Reaction mentioning
confidence: 99%
“…43 Additionally, in the work by Fang et al NaOH turned out to be an ineffective aldol catalyst, when used under hydroformylation conditions. 19 In the same work, the authors found a combination of pyrrolidine and benzoic acid to be the most successful aldol catalyst for their reaction system. The pyrrolidine enables enamine catalysis, while the benzoic acid accelerates the enamine formation.…”
Section: Catalysis In Watermentioning
confidence: 96%
“…In 2014 Beller and co-workers presented a homogeneous catalyst system for the hydroformylation/aldol condensation tandem reaction. 19 The group took advantage of a rhodium/phosphine hydroformylation catalyst in combination with a pyrrolidine-based organocatalyst for the aldol step. With this system, they were able to convert a variety of olefins to the corresponding aldol products with high conversions and selectivity.…”
Section: Introductionmentioning
confidence: 99%
“…The compatibility of the different reaction parameters required for each individual reaction step poses a significant challenge when it comes to developing new tandem catalysis reactions. Tandem reactions such as hydroaminomethylation, hydrohydroxymethylation,, aldol condensation or epoxidation all include a hydroformylation step to obtain the intermediate aldehyde, which then undergoes further conversions to achieve the desired product. Recent investigations using a rhodium and ruthenium catalyst have combined dcpd hydroaminomethylation with the dealkylation of the resulting secondary amines with ammonia to obtain TCD‐diamine.…”
Section: Introductionmentioning
confidence: 99%